Evaluating laboratory screening tests for malaria on blood donors candidates to reduce the risk of transfusion-transmitted malaria in an endemic area of Indonesia (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND Laboratory screening of blood donors for malaria has not been routinely performed in Indonesia. Current policy and practice simply exclude donors based on a history of active clinical malaria. This study was aimed to evaluate laboratory screening tests for malaria among blood donors in an endemic area of Indonesia. METHODS The study was conducted on 550 consecutive blood samples withdrawn from volunteer donors at the Red Cross Blood Transfusion Unit in Ambon city using microscopic and rapid diagnostic tests for antigen as well as for antibody. Furthermore, 248 of those 550 samples were also tested for the presence of malaria DNA using 18S rRNA marker. Statistical analysis was done descriptively using SPSS software version 15 (SPSS Inc., USA). RESULTS The overall malaria positivity rate among the donors was 4.5% (25/550). None of the specimens tested using microscopy or rapid test for malaria antigen assay were positive. However 22 (4.0%) samples were positive for malaria antibody against Plasmodium falciparum; while 3 (1.2%) were positive by PCR. CONCLUSIONS Laboratory testing for blood donors may be used to prevent transfusiontransmitted malaria in an endemic area of Indonesia.